2002
DOI: 10.1063/1.1515108
|View full text |Cite
|
Sign up to set email alerts
|

Knudsen forces on microcantilevers

Abstract: When two surfaces at two different temperatures are separated by a distance comparable to a mean-free path of the molecules of the ambient medium, the surfaces experience Knudsen force. This mechanical force can be important in microelectromechanical systems and in atomic force microscopy. A theoretical discussion of the magnitude of the forces and the conditions where they can be encountered is discussed. A potential application of the Knudsen force in designing a cantilever-based vacuum gauge is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Both the frequency and the bending undergo variations as a function of the pressure. Although the origin of such variations is still under investigation, the acquired data are in accordance with the reported results, where similar variations in the frequency and bending as a function of pressure and temperature were examined in various pressure regimes from the continuum to free molecular [19][20][21][22][23]. Fig.…”
Section: Effects Of Ambient Mediasupporting
confidence: 80%
“…Both the frequency and the bending undergo variations as a function of the pressure. Although the origin of such variations is still under investigation, the acquired data are in accordance with the reported results, where similar variations in the frequency and bending as a function of pressure and temperature were examined in various pressure regimes from the continuum to free molecular [19][20][21][22][23]. Fig.…”
Section: Effects Of Ambient Mediasupporting
confidence: 80%
“…The flexural phonon flux flowing from hot to cold cedes some of its physical momentum by scattering onto the adsorbed cluster, which is ballistically transported. Previously known examples of ballistic phoresis include the Knudsen force exerted by gas particles on tips, described by Passian et al (52) and observed by Gotsmann and Dürig (53). The phonon-induced ballistic thermophoresis described here is specific to submicrometer sheet sizes and will eventually disappear as flexural phonons evolve from ballistic to diffusive once the sheet length L is large enough, a crossover which our simulations do not yet detect at L ∼ 150nm.…”
Section: Discussionmentioning
confidence: 76%
“…A similar problem has been investigated using DSMC or another kinetic approaches in [9][24]- [30]. In the following we shall consider the effects of Knudsen number and convection on heat transfer from the heated plate using finite difference numerical solutions of macroscopic methods.…”
Section: Introductionmentioning
confidence: 99%